2015
DOI: 10.1111/idj.12165
|View full text |Cite
|
Sign up to set email alerts
|

Decision making in third molar surgery: a survey of Brazilian oral and maxillofacial surgeons

Abstract: This study was designed to evaluate the variations in decision making among Brazilian oral and maxillofacial surgeons (OMFS) and trainees in relation to third molar surgery. A survey on 18 diverse clinical situations related to the assessment and treatment of the third molar surgeries was conducted during the 20th Brazilian National OMFS meeting. Participants were divided into three groups according to their level of training. Another variable studied was length of experience. Correlation between the question … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 27 publications
0
11
0
3
Order By: Relevance
“…Although a substantial number of clinical studies have been published on this topic, the conflicting results still hinder the decisionmaking process in the clinical setting (18,22). These controversial findings are the product of differences among the studies, regarding to diverse methodological issues, such as study design, sample size or monitoring (follow-up) time (6,18). Additionally, Friedman (7) expresses that, even currently, five "historical" myths regarding third molars prevail among the dental community: (i) third molars have a high incidence of pathology; (ii) early removal of third molars is less traumatic; (iii) pressure of erupting third molars causes crowding of anterior teeth; (iv) the risk of pathology in ITM increases with age; and (v) there is little risk of harm in the removal of third molars.…”
Section: Need For Prophylactic Removal Of Asymptomatic Third Molarsmentioning
confidence: 99%
See 3 more Smart Citations
“…Although a substantial number of clinical studies have been published on this topic, the conflicting results still hinder the decisionmaking process in the clinical setting (18,22). These controversial findings are the product of differences among the studies, regarding to diverse methodological issues, such as study design, sample size or monitoring (follow-up) time (6,18). Additionally, Friedman (7) expresses that, even currently, five "historical" myths regarding third molars prevail among the dental community: (i) third molars have a high incidence of pathology; (ii) early removal of third molars is less traumatic; (iii) pressure of erupting third molars causes crowding of anterior teeth; (iv) the risk of pathology in ITM increases with age; and (v) there is little risk of harm in the removal of third molars.…”
Section: Need For Prophylactic Removal Of Asymptomatic Third Molarsmentioning
confidence: 99%
“…However, diverse studies have demonstrated considerable intra-and inter-dentist variability -including wrong diagnosis-concerning to decisions to extract or not asymptomatic impacted third molars (9,24). Regarding this, the criteria defining the indications for the surgical extraction of these molars are still the origin of considerable debate among dental practitioners (6,8,9,19). Due to these reasons, diverse clinical practice guidelines have been developed in an attempt to increase the professional performance, and to assist the clinicians, patients and parents in making decisions about the appropriate management of ITM (22).…”
Section: Indications For the Surgical Extractionmentioning
confidence: 99%
See 2 more Smart Citations
“…No contexto da cirurgia bucomaxilofacial, a exodontia de terceiros molares é um dos procedimentos mais comuns, apresentando diversas indicações [1][2][3][4][5][6] . É um procedimento delicado, podendo causar diversas complicações pós-operatórias 7,8 .…”
Section: Introductionunclassified